1999
DOI: 10.1051/animres:19990402
|View full text |Cite
|
Sign up to set email alerts
|

Feed intake behaviour of group-housed Piétrain and Large White growing pigs

Abstract: -Feed intake behaviour traits were recorded on 210 Large White and 114 Pietrain entire male pigs housed in single-breed groups (range of group size: 8-13) and having 24 h access to 'Acema 48' electronic feed dispensers. Three stages of growth were considered (average body weights of 39, 64 and 89 kg for both breeds), and feeding behaviour traits were calculated separately for two periods of the day (8-20 h and 20-8 (34.8 vs. 38.1 g ' min ' ', ', P < 0.01 Average time per meal (9.4 min), however, was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 19 publications
5
17
0
Order By: Relevance
“…Estimated effects were in the usual range of literature estimates (Larzul et al, 1997). Labroue et al (1999) found a lower DFI, by 19%, in the PI breed compared with the LW breed, which would correspond to 2 to 3 s.d. of the trait, and reported a small difference in feed efficiency between the two breeds.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Estimated effects were in the usual range of literature estimates (Larzul et al, 1997). Labroue et al (1999) found a lower DFI, by 19%, in the PI breed compared with the LW breed, which would correspond to 2 to 3 s.d. of the trait, and reported a small difference in feed efficiency between the two breeds.…”
Section: Discussionsupporting
confidence: 55%
“…Labroue et al, 1994Labroue et al, , 1999. The halothane mutation was segregating in all the sire families.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Pietrain piglets had a poorer FCR during week 3 compared to the other 2 genotypes, indicating that they used their feed less efficiently than the Hampshire and Large White piglets, or perhaps that Pietrain piglets were wasting more feed due to differences in feeding behaviour among the genotypes. Studies have demonstrated differences between genetic lines in terms of feeding patterns such as changes in feed consumption and frequency of feeder visits (Augspurger et al, 2002;Labroue et al, 1999). Labroue et al (1999) found that Pietrain boars visited the trough much less frequently but for longer periods of time compared to Large White boars.…”
Section: Discussionmentioning
confidence: 99%
“…For example, with a fast of 48 h, the serum isoflavone level was reported to increase by 1.7-fold compared to that of nonfasted mice [29]. It is not known whether an overnight fast in pigs would have any significant effect on the pharmacokinetics of isoflavones in this species, especially when pigs are known to consume only small amounts of feed at night [30]. Further research is needed to fully investigate the impact of the duration of fasting on the pharmacokinetics of isoflavones in pigs.…”
Section: Discussionmentioning
confidence: 99%